BEAUTY CONCEPT REPRESENTED ON COSMETIC ADVERTISEMENT - Diana Rahmawati (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2019)
The issues surrounding beauty concepts such as related to women in color, how society make their own standard of beauty and how its prevalence in any mass media’s advertisements deserve our attention. Fenty Beauty tried to handle those problems related to skin tone and beauty standards. The objectives of this research were to analyze how the cosmetic advertisement represent beauty concepts according to semiotics signs, and to decipher messages conveyed by verbal (tagline) and visual signs in cosmetic advertisement represent beauty concept. The participants of this research are Rihanna and eleven models in Fenty Beauty advertisement video in each scenes. The Fenty Beauty video itself captured woman with different skin tones, hair, body sizes, ethnicity and religion. To obtain the data the researcher used two instruments namely video observation, and documents analysis. The findings investigating the beauty concepts cover the skin tones, make up, hair and face symmetry. Meanwhile, the finding examining messages there verbal and visual sign. Verbal sign was found  in two types. The first is ‘the new generation of beauty’. It means as freedom of expression in creating beauty looks based on their apparences. The second is ‘Fenty Beauty by Rihanna’, it means beauty is something personality. The messages are conveyed in visual signs are everyone is beautiful in their own way with what is God already given. There’s no concrete standard for beauty relate to skintone, hairs and face symmetry. The natural make up always makes someone more gorgeous. Furthermore, the researcher would also suggest further research to incorporate readers to think critically and open-minded what they see in cosmetic advertisement.